Pedunculoside targets P2X7R to protect against myocarditis by regulating the NLRP3/PIP2/MAPK signaling pathway - Zhuo, Youqiong; He, Jia; Wang, Qin-Qin; Xiao, Yuntian; Xie, Xiaoyun; Liu, Lina; Yang, Shilin; Li, Jingjing; Yuan, Renyikun; Gao, Hongwei (Frontiers in Pharmacology, 2025)
BackgroundMyocarditis is an inflammation of the myocardium caused by a variety of reasons, with myocardial cell necrosis and interstitial inflammatory cell infiltration as the main manifestations. Pedunculoside (PE) plays a protective role in inflammatory diseases; however, it’s effect and mechanism on myocarditis remains unexplored.MethodsIn this study, we evaluated the cardioprotective effects of PE in vivo and in vitro using the LPS + ATP-induced cardiomyocyte injury model and the LPS-induced rat myocarditis model, and elucidated its potential mechanism.ResultsWe found that PE demonstrated inhibition of H9c2 cell death and decreased ROS, Ca2+ levels, and MMP loss induced by LPS + ATP. Moreover, PE improved cardiac function in LPS-induced myocarditis rats. Mechanistically, PE suppressed the activation of the NLRP3 inflammasome, PIP2, and MAPK signaling pathways, which are associated with P2X7R. Additionally, PE interfered with and attenuated the interaction between P2X7R and PIP2, displaying strong docking activity with P2X7R.ConclusionTaken together, PE exhibited significant anti-myocarditis activity by interacting with P2X7R and inhibiting the NLRP3, PIP2, and MAPK pathways, highlighting its potential as a therapeutic agent for clinical myocarditis treatment.